Physiological changes leading to obesity in active 13-lined ground squirrels (Ictidomys tridecemlineatus) - Sonsalla, Michelle (My University, 2018)
Obesity is a significant health issue in the developed world. During the pathogenesis of obesity, drastic changes in the gut microbiota lead to intestinal inflammation and increased intestinal permeability, resulting in chronic, low-grade inflammation in white adipose tissue that leads to fattening and insulin resistance. 13-lined ground squirrels (Ictidomys tridecemlineatus) naturally fatten in preparation for hibernation and thus we propose that they may be a good model for weight gain in humans. We studied 13-lined ground squirrels during their active season and monitored calorie consumption, body mass, glucose tolerance, adipose mass, and adipose inflammation. Calorie consumption peaked nine weeks after emergence then decreased, whereas body mass continued to increase until weeks 13-15 before it leveled off. Glucose tolerance was relatively constant for most of the active season, with a spike in glucose intolerance 18 weeks post-emergence before returning to similar levels as before. Adipose samples from squirrels were collected throughout the active season and analyzed using qRT-PCR and ELISA to determine changes in immune state. Adipose tissue exhibited significant shifts in immune cell and cytokine levels during the development of obesity. These results suggest that changes in weight gain continue after food intake decreases and adipose immune state during the development of obesity in 13-lined ground squirrels follow the same progression as in other animal models, displaying levels of chronic, low-grade inflammation during obesity.
"A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science - Biology"
Keywords: Squirrels; Obesity